Correlation Between High-sensitivity C Reactive Protein and Local Arterial Stiffness Measured by Radio Frequency Echotracking System in Type 2 Diabetic Patients - Azri Nurizal; Dono Antono; Ika P Wijaya; Hamzah Shatri (Acta Medica Indonesiana)
Aim: to identify the correlation between hsCRP and arterial stiffness in type-2 diabetic patients. Methods: a cross-sectional study was conducted to assess the plasma levels of hsCRP and carotid arterial stiffness in 40 patients with type-2 diabetes mellitus. The common carotid artery stiffness was evaluated using radio frequency echo-tracking system to determine the local carotid pulse wave velocity (carotid-PWV). Results: median value of hsCRP in this study was 4.5 (0.2 to 18.9) mg/L and the average value of local carotid stiffness was 8.8±1.7 m/sec. High sensitive CRP showed a strong correlation with carotid-PWV (r=0.503, P=0.001). hsCRP level was independently associated with carotid-PWV after adjustment for age, body mass index, and mean arterial pressure (r=0.450, P=0.005). Conclusion: hs-CRP has moderate positive correlation with arterial stiffness in patients with type-2 diabets mellitus.